Direct solar-to-hydrogen generation by quasi-artificial leaf approach: possibly scalable and economical device - Patra, Kshirodra Kumar; Bharad, Pradnya Arunrao; Jain, Vanshika; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2019)
Often, a disadvantage in one area of science may become an advantage in another area. In contrast, a successful concept in one area could work for a complementary area of research too. These two philosophies have been successfully used for solar hydrogen generation and they underscore the necessity to connect relevant concepts. We, herein, report a quasi-artificial leaf (QuAL) device in a wireless configuration with a TiO2/Mn-CdS composite and NiCu as a co-catalyst for possibly scalable as well as commercially viable solar hydrogen production under one sun conditions. The device works at no applied potential and generates 10.5 mL h(-1) (16 mL h(-1)) H-2 with Ni5Cu2.5 alloy (Pt) as a co-catalyst, which corresponds to a power conversion efficiency (PCE) of 4.8% (7.3%). The significant resemblance of NiCu alloy to Pt in terms of its electrochemical activity and electronic structure makes the device more economical. While the millisecond lifetime of electrons in Mn-CdS is known to help for white light emission, the same factor helps to greatly improve charge utilization for H-2 production in the QuAL device. In contrast, the reabsorption of emitted light is a vexing problem in emission applications; however in the present work, reabsorption is successfully utilized to enhance hydrogen yield. Spectroscopy techniques combined with electrocatalytic studies were employed and the results correlated with solar hydrogen generation, demonstrating this as a new pathway to design better solar-light-harvesting architectures.

Enhanced hydrogen fuel production using synergistic combination of solar radiation and TiO2 photocatalyst coupled with Burkholderia cepacia lipase - de Souza Brandao, Luma Mirely; Barbosa, Milson dos Santos; de Jesus, Roberta Anjos; Bharad, Pradnya Arunrao; Lima, Alvaro Silva; Faria Soares, Cleide Mara; Navarro Yerga, Rufino Manuel; Bilal, Muhammad; Romanholo Ferreira, Luiz Fernando; Iqbal, Hafiz M. N.; Gopinath, Chinnakonda S.; Figueiredo, Renan Tavares (International Journal of Hydrogen Energy, 2022)
Promising and sustainable alternatives for hydrogen production have been investigated. Among these, the use of enzymes may represent an efficient alternative. In this work, an increase in hydrogen production under simulated sunlight by combining TiO2 and TiO2/MgCl2 with Burkholderia cepacia lipase (BCL) was reported. The samples (TiO2, TiO2/MgCl2, and TiO2 /MgCl2/BCL) were characterized by X-ray diffraction (XRD), thermo-gravimetric (TGA), N-2 adsorption-desorption isotherms (BET), scanning electron microscopy (SEM), and UV-Visible absorption spectra. Hydrogen production tests were performed in aqueous methanol solutions under simulated sunlight. The results demonstrated that 130-times greater increase in hydrogen production rate was observed by the addition of BCL than individual TiO2. This better hydrogen production rate can be attributed to the increase in the amount of reduction equivalent of the system due to the oxidation of protein peptides caused by TiO2. In conclusion, the results indicate that hydrogen production efficiency can be significantly improved when integrating TiO2/MgCl2 with BCL. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: hydrogen production; Lipase; Nano-conjugated enzymes; Photocatalyst; Solar radiation; Titanium dioxide